2018
DOI: 10.1098/rsta.2017.0380
|View full text |Cite
|
Sign up to set email alerts
|

Early models of chemical oscillations failed to provide bounded solutions

Abstract: Before the development of the Brusselator, the Sel'kov and Turing models were considered as possible prototype models of chemical oscillations. We first analyse their Hopf bifurcation branches and show that they become vertical past a critical value of the control parameter. We explain this phenomenon by the emergence of canard orbits. Second, we analyse all solutions in the phase plane and show that some initial conditions lead to unbounded trajectories even if there exists a locally stable attractor. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has been shown that the basic Selkov system admits solutions with unbounded oscillations and that the diameter of the image of a periodic solution can tend to infinity as approaches a finite limit, thus completing the results of Brechmann and Rendall ( 2018 ) on that system and rigorously confirming a claim made in Selkov ( 1968 ). Note that some statements related to this issue have been made in Erneux ( 2018 ) but that reference does not contain rigorous proofs of those statements. One remaining question is that of the rate with which the diameter of the image of the periodic solution tends to infinity as the critical parameter value is approached.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the basic Selkov system admits solutions with unbounded oscillations and that the diameter of the image of a periodic solution can tend to infinity as approaches a finite limit, thus completing the results of Brechmann and Rendall ( 2018 ) on that system and rigorously confirming a claim made in Selkov ( 1968 ). Note that some statements related to this issue have been made in Erneux ( 2018 ) but that reference does not contain rigorous proofs of those statements. One remaining question is that of the rate with which the diameter of the image of the periodic solution tends to infinity as the critical parameter value is approached.…”
Section: Discussionmentioning
confidence: 99%
“…The Brusselator model consists of a single nonlinear (three molecules) reaction that describes the evolutionary process of two chemical intermediates X and Y [ 29 ]. The model is a mathematical model, which can be used to simulate the self-organizing phenomenon of a given system and identify whether the system achieves a dissipative structure accurately and rationally [ 30 ].…”
Section: Model and Datamentioning
confidence: 99%
“…Computer simulations were also reported 13 confirming the occurrence of patterning behaviours in the instability domain of the model; the drawback that locally some component's concentration becomes negative during such evolution could be put right numerically by resetting negative values equal to zero when they appear. Satisfactory, stable patterns are then finally obtained under those conditions (for a mathematical analysis of the drawbacks exhibited by the early models of Turing, see [67,68]).…”
Section: Dissipative Structures (1967)mentioning
confidence: 99%